REVOLUSI PEMBERDAYAAN PETANI/KELOMPOK TANI (FARMERS / FARMER GROUPS EMPOWERMENT REVOLUTION) - Handriyanto, Imawan Eko (Jurnal Ilmu-Ilmu Pertanian, 2008)
The empowerment of farmer is one of the objectives in agricultural development. Several government programs focusing on farmers empowerment fail to meet their expected goals, due to the farmersdifferent responses towards the variety of programs and facilities provided by the government as well as other institutions. Accordingly, a suitable formulation to improve facilitation is called for.